PENGEMBANGAN MEDIA ANIMASI DUA DIMENSI BERBASIS JAVA SCRATCH MATERI TEORI KINETIK GAS UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA SMA (UPEJ Unnes Physics Education Journal, 2013)
The purposes of this research are to create and develope a instructional media with two dimentional animationbased on Java Scratch theory of kinetic gases topic and to know description of skill and instructional media’seffectiviy in increasing concept’s understanding of senior high school students to theory of kinetic gases topic.This study is research and development based on 4D models consisted of four steps, they are definition, design,develope, and disseminate. Methods of data collected use questionnaire and documentation. Results of researchand testing by the validator most likely to material substance aspects, aspects of instructional design, softwareengineering aspect, and aspects of visual communication design is good. To program testing by students is goodenough and result program testing by teacher is good. The result of students responses’ analysis to learningimplementation with program is accepted well by students and students curiosity’s grade shown by averagescore of respondents that agree about application of this program.